1983
DOI: 10.1042/bj2150483
|View full text |Cite
|
Sign up to set email alerts
|

Guinea-pig kidney β-N-acetylgalactosaminyltransferase towards Tamm-Horsfall glycoprotein. Requirement of sialic acid in the acceptor for transferase activity

Abstract: A beta-N-acetylgalactosaminyltransferase that preferentially transferred N-acetylgalactosamine to Sd(a-) Tamm-Horsfall glycoprotein was found in guinea-pig kidney microsomal preparations. This enzyme was kidney-specific and was able to transfer the sugar to other glycoproteins, such as fetuin and alpha 1-acidic glycoprotein. The presence of sialic acid in the acceptors was essential for the transferase activity when either glycoproteins or their Pronase glycopeptides were used as acceptors. Two glycopeptides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…As in previous reports on Cad-active mucins (Blanchard et al, 1983;Herkt et al, 1985;Nasir-Ud-Din et al, 1986) and Sd"-active T-H glycoprotein (Donald et al, 1983;Donald and Feeney, 1986;Williams et al, 1984), no terminal GalNAcfll-4GalPl-or NeuSAca2-6(GalNAc/Il~ 4)Gal/II-element was found. This is in agreement with biosynthetic studies with fi-N-acetylgalactosaminyltransferases from guinea-pig kidney (Serafini-Cessi and Dall'Olio, 1983), human kidney (Piller et al, 1986), human blood plasma (Takeya et al, 1987) and human urine (Serafini-Cessi et al, 1988), which have demonstrated that the transferases require a2 -3-linked sialic acid in the acceptor.…”
Section: Discussionsupporting
confidence: 77%
“…As in previous reports on Cad-active mucins (Blanchard et al, 1983;Herkt et al, 1985;Nasir-Ud-Din et al, 1986) and Sd"-active T-H glycoprotein (Donald et al, 1983;Donald and Feeney, 1986;Williams et al, 1984), no terminal GalNAcfll-4GalPl-or NeuSAca2-6(GalNAc/Il~ 4)Gal/II-element was found. This is in agreement with biosynthetic studies with fi-N-acetylgalactosaminyltransferases from guinea-pig kidney (Serafini-Cessi and Dall'Olio, 1983), human kidney (Piller et al, 1986), human blood plasma (Takeya et al, 1987) and human urine (Serafini-Cessi et al, 1988), which have demonstrated that the transferases require a2 -3-linked sialic acid in the acceptor.…”
Section: Discussionsupporting
confidence: 77%
“…It is therefore expected that the (fl -4)GalNAc transferases involved in biosynthesis of Cad and Sda antigens might also be different. (,/1-4)GalNAc transferases were recently reported in guinea-pig kidney (Serafini-Cessi & Dall'Olio, 1983) and in a murine cytotoxic T-cell line (Conzelmann & Kornfeld, 1984) and both enzymes were able to transfer [14C]GalNAc from UDP-[14C]GalNAc to human glycophorin as expected for the blood group Cad enzyme. However, experiments from our group suggest that the (/1l-4)GalNAc from human kidney has a different substrate specificity since it is inactive towards native or partially desialylated and/or resialylated glycophorin A preparations.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, it has been shown that β1,4-N-GalNActransferase requires the presence of NeuAc (not NeuGc) α2-3-linked to Gal for its task of adding the immunodominant sugar [84][85][86]. The tissue distribution of this β1,4-N-GalNActransferase (also termed Sd a -transferase and homologous to the murine CT transferase [87]) correlates with the tissue localization of the Sd a antigen, namely, it is particularly abundant in the human kidney and colon, and a soluble form is present in urine from Sd(a+) individuals [88][89][90].…”
Section: Sd a Carbohydrate Antigenmentioning
confidence: 99%